2021
DOI: 10.1186/s41065-021-00183-z
|View full text |Cite
|
Sign up to set email alerts
|

RTP4 is a novel prognosis-related hub gene in cutaneous melanoma

Abstract: Objective Melanoma accounts for 80% of skin cancer deaths. The pathogenesis of melanoma is regulated by gene networks. Thus, we aimed here to identify gene networks and hub genes associated with melanoma and to further identify their underlying mechanisms. Methods GTEx (normal skin) and TCGA (melanoma tumor) RNA-seq datasets were employed for this purpose. We conducted weighted gene co-expression network analysis (WGCNA) to identify key modules and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Previous studies have suggested that RTP4 helps the GPCR oligomer properly assemble in the endoplasmic reticulum, promotes the dimerization of receptors in the Golgi apparatus, and decreases the ubiquitination of the heterodimers [ 29 ]. Other studies have shown that the RTP4 was overexpressed in some connective tissue disorders and parasitic infections [ 30 , 31 ] and correlated with some cancers [ 32 , 33 ]. That RTP4 induced by IFN-I could explain this phenomenon and is associated with immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that RTP4 helps the GPCR oligomer properly assemble in the endoplasmic reticulum, promotes the dimerization of receptors in the Golgi apparatus, and decreases the ubiquitination of the heterodimers [ 29 ]. Other studies have shown that the RTP4 was overexpressed in some connective tissue disorders and parasitic infections [ 30 , 31 ] and correlated with some cancers [ 32 , 33 ]. That RTP4 induced by IFN-I could explain this phenomenon and is associated with immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, methylated RTP4 can be considered as a new biomarker for precise diagnosis and treatment of prostate cancer [ 37 ] and RTP4 can be considered as an independent indicator to judge the prognosis of oral cancer [ 38 ]. RTP4 has also been reported that it is significantly associated with immune cell infiltration and immune checkpoint encoding genes (PDCD1, TIM-3, and LAG3) in melanoma [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent documents have revealed 4 key genes as guardians who actively participate in the protective immunity of various inflammatory diseases and cancer ( Li et al, 2021a ). IFI44 is found on human chromosome 1p31.1 ad belongs to the interferon-stimulated gene (ISG), which plays a significant role in immunoregulation and tumor cell recognition ( Lukhele et al, 2019 ; Wang et al, 2020 ; Li et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…RTP4 (Receptor Transporter Protein 4) is a member of the RTPs family that is directly involved in modulating the expression of cell-surface G-coupled protein receptors ( Saito et al, 2004 ; Boys et al, 2020 ). Several studies have found that RTP4 is strongly linked to a virus defense response and cancer prognosis ( Li et al, 2021a ). Following Lipinski’s rule-of-five for drug likeliness, a protein’s druggability is solely determined by its affinity and specificity for small molecules ( Abi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…RTP4 (Receptor transporter protein 4) as an innate antiviral effector [ 33 ], it was related to the flavivirus replication, binds viral RNA, and inhibits viral genome amplification [ 34 ], and plays a role in diverse viral infections [ 35 ]. In addition, Li et al reported that RTP4 was associated with immune cell infiltration [ 36 ]. This suggests that RTP4 might be involved in immunity response process, while previous study indicated that activation of the immune response results in low feed efficiency due to increased maintenance requirements [ 26 , 37 ].…”
Section: Discussionmentioning
confidence: 99%